1997
DOI: 10.1108/09649429710162884
|View full text |Cite
|
Sign up to set email alerts
|

A study of the tournament model with female managers

Abstract: Reports the findings of the first study to test the tournament model of careers with female managers. Follows the careers of 3,800 women in a large internal labour market firm. Investigates the signals of early promotions, career velocity, education, tenure and entering position. Examines the relationships between these signals and career attainment. The results do not show the strong support of the tournament model that research with men has found. Using the variables previously found in the literature to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Although we think that we have shown the productive use of a social capital perspective when predicting gendered career reins, there could be a bias in the theory that biased our results. In a study of the tournament model, Hurley & Sonnenfeld (1997) found less support for the model among female managers than studies of male hierarchies have found, thus indicating that the model is more adapted to males. The perspective of social capital that we use has, rightly or wrongly, been condemned as having a political bias: ‘Social capital offers answers which are simple, nostalgic and conservative.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although we think that we have shown the productive use of a social capital perspective when predicting gendered career reins, there could be a bias in the theory that biased our results. In a study of the tournament model, Hurley & Sonnenfeld (1997) found less support for the model among female managers than studies of male hierarchies have found, thus indicating that the model is more adapted to males. The perspective of social capital that we use has, rightly or wrongly, been condemned as having a political bias: ‘Social capital offers answers which are simple, nostalgic and conservative.…”
Section: Discussionmentioning
confidence: 91%
“…The literature does not offer any guidance whether to expect this factor to be gendered or not. One study (Hurley & Sonnenfeld, 1997) found frequent changes to influence career attainment of females according to the tournament model. It could be argued that if a woman has a tendency to have low expectations of advancement due to her gender, the attention gained by being promoted will increase self-esteem more for a woman than for a man, since promotion meets a man's expectations.…”
Section: Change Of Positionmentioning
confidence: 99%
“…Similarly, in a study of womenÕs career patterns, Huang and Sverke (2007) found that womenÕs occupational paths were diverse, represented by patterns of upward mobility, stability, downward mobility, and fluctuation. Hurley and Sonnenfeld (1997) found that the ÔtournamentÕ model of careers as a series of wins and losses in a race to the top did not apply to women to the same degree as men. The authors suggested that women in organizations may end up being placed in fundamentally different tournaments than men.…”
Section: Paradox 2: Families Continue To Be Liabilities To Womenõs Camentioning
confidence: 95%
“…Interpersonal conflicts are a more common frame for negotiations than intrapersonal deliberation, but gendered social order is often negotiated across multiple levels. For example, models of organizations as tournaments (Capelli & Casio, 1991; Hurley & Sonnenfeld, 1997) in which individual organizational members compete with each other for a few spots at the top may be revealed as inherently gendered. The paucity of women in upper management positions and feminization of entire fields suggests that negotiation might work differently than most negotiation researchers think.…”
Section: Who What How When and Whymentioning
confidence: 99%